Viabilidade econômica para instalação de energia fotovoltaica nos órgãos públicos e escolas do município de Tio Hugo - Machado, Ana Rita Ferreira (2022)
The great potential for the development of solar energy in Brazil, associated with the recent regulations of distributed generation, made it possible for consumers to not only generate their own energy, but also to develop business in the solar energy sector. The present work aims to make a study addressing the main technical and economic requirements for the construction of a photovoltaic station in the Municipality of Tio Hugo/RS. Throughout the work, the design and choice of the main components of the photovoltaic system was carried out, starting from the choice of the station installation location, photovoltaic modules, inverters and fixing structure. The photovoltaic generation system was budgeted at R$ 533,251.32 with an aggregate of R$ 107,568.84 corresponding to the construction of the fence and fencing, monitoring of the station area. The feasibility of the project was based on the estimates of the total cost of implantation and operation of the station, in the time of 25 years using financial indicators such as Payback, IRR, NPV. The payback obtained the financial return in 4 years, the IRR generated a value of 26%. The implantation of the plant presented good financial results.